Sự tham gia của sinh viên vào hoạt động thảo luận nhóm trong nhóm trong giờ học nói Tiếng Anh ở FELTE - ULIS - VNU - Nguyễn, Thu Hiền (2020)
Group discussion has been widely implemented in EFL classrooms in Vietnamese tertiary context as an effective strategy in the development of students ‟communicative competence. Though the implementation of group discussion has been explored by prior researchers from different perspectives, the level of students‟ participation in this activity has not been shed light on with adequate research. This study sought to occupy this research space by investigating the level of students‟ participation in group discussion in English-speaking lessons and identifying the affecting factors as well. This study was conducted with a total of 101 students at the Faculty of English Language Teacher Education – University of Languages and International Studies – Vietnam National University, Hanoi. Both quantitative and qualitative methods were adopted. Drawing on the data collected by means of the questionnaire, obser vationand interview, several findings were registered. The results of the study indicated that though a majority of students participated in the activity, the participation frequency and quality remained at a rather low level. The level of participation among individuals also varied significantly. A number of factors were identified a sexerting impacts on their participation, including students‟ attitude towards the value of group discussion, linguistic factors, pedagogical factors, personality, and socio-cultural factors. Among these factors, linguistic elements, discussion topics, knowledge preparation and the lack of confidence emerged as the major determinants of students‟ participation in group discussion. From these findings, pedagogical implications and recommendations for future studies were put forward.